An assessment of the subgeneric classification of Zygophyllum (Zygophyllaceae) in Southern Africa : evidence from noncoding trnL-trnF chloroplast DNA sequences - Makwarela, Azwimpheleli M. (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.(Systematics and Biodiversity Science))-- Stellenbosch University, 2001.